2003
DOI: 10.1016/j.clpt.2003.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Implication of cholesterol in cyclosporine pharmacodynamics in minimal change nephrotic syndrome

Abstract: The data raised the possibility that hypercholesterolemia in patients with minimal change nephrotic syndrome attenuates cellular and clinical cyclosporine pharmacodynamics. Down-regulation of LDL receptor in T cells was not observed in these patients, and individual deviation of PBMC response to cyclosporine does not appear to be related to the difference of LDL receptor-positive cell numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…1,4 From this point of view, individualization of immunosuppressive therapy based on the patient sensitivity to the suppressive efficacy of the drugs estimated using PBMCs of patient origin before transplantation has been improved to prevent acute allograft rejection episodes. 1,12,18 Powerful immunosuppressive therapy based on the combined use of calcineurin inhibitors with glucocorticoids and antimetabolites also improved the clinical outcome of renal transplantation. For successful long-term renal transplantation, however, several side effects of these drugs, especially glucocorticoids, should be considered, and, accordingly, safety glucocorticoid reduction/withdrawal is one of the most important issues for successful long-term immunosuppressive therapy in renal transplantation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1,4 From this point of view, individualization of immunosuppressive therapy based on the patient sensitivity to the suppressive efficacy of the drugs estimated using PBMCs of patient origin before transplantation has been improved to prevent acute allograft rejection episodes. 1,12,18 Powerful immunosuppressive therapy based on the combined use of calcineurin inhibitors with glucocorticoids and antimetabolites also improved the clinical outcome of renal transplantation. For successful long-term renal transplantation, however, several side effects of these drugs, especially glucocorticoids, should be considered, and, accordingly, safety glucocorticoid reduction/withdrawal is one of the most important issues for successful long-term immunosuppressive therapy in renal transplantation.…”
Section: Discussionmentioning
confidence: 98%
“…12 The clinical usefulness of the cellular pharmacodynamic approaches of immunosuppressive drugs using PBMCs of patient origin for patient-tailored drug therapy has also been demonstrated in the reports including those of our institutions. [13][14][15][16][17][18][19] In the present study, we evaluated PBMC response to 4 immunosuppressive drugs: hydrocortisone (cortisol), methylprednisolone, cyclosporine, and tacrolimus in vitro in 44 consecutive renal transplant recipients who are undergoing a schedule of reduction/withdrawal of glucocorticoid treatment. PBMC responses to these drugs were retrospectively related to allograft function after reduction or withdrawal of glucocorticoid, and possible biomarkers of the safety glucocorticoid reduction were established.…”
Section: Introductionmentioning
confidence: 99%
“…Hirano et al [2] reported that hypercholesteraemia in patients with minimal change nephrotic syndrome attenuated cellular and clinical CsA pharmacodynamics. The levels of total cholesterol and LDL cholesterol impaired 50% inhibition (IC50) of peripheral blood mononuclear cells (PBMC) blastogenesis in minimal change nephrotic syndrome [2]. CsA tends to bind with LDL cholesterol in plasma because of its hydrophobicity.…”
Section: Discussionmentioning
confidence: 98%
“…The hyperlipidaemia associated with nephrotic syndrome affects the pharmacokinetics of steroids and CsA [1,2], and diminishes the immunosuppressive effect of CsA [2]. Low-density lipoprotein (LDL) apheresis is effective in some children with steroid-resistant nephrotic syndrome (SRNS) [3].…”
Section: Introductionmentioning
confidence: 99%
“…20 La hiperlipidemia asociada con el síndrome nefrótico afecta la farmacocinética y disminuye el efecto inmunosupresor de la ciclosporina. 21 Se ha reportado la probable mejoría de la farmacocinética de la ciclosporina con el tratamiento concomitante con pravastatina, lo que llevó a la remisión del síndrome nefrótico en una paciente en Japón; 22 de forma similar a lo descrito en el caso clínico número dos no se había alcanzado remisión del síndrome nefrótico hasta el inicio del tratamiento con estatinas. Sin embargo, el efecto de los hipolipemiantes sobre el grado de proteinuria no se ha demostrado en estudios controlados aleatorizados.…”
Section: Discussionunclassified